IELTS preparation and practice : reading and writing : general training module - Pejovic, Vladimir; Niclin, Michael; Read, Peggy; Vũ Tài Hoa; Nguyễn Văn Phước (Đà Nẵng : Nxb Đà Nẵng, 2003)
General training reading; General training writing.
Keywords: English language; International English Language Testing Systems; English language -- Textbooks for foreign speakers; International English Language Testing System; English language -- Examinations, questions, etc